AUDIO MUROTTAL TERAPI PADA PASIEN POST OPERASI SECTIO CAESAREA DENGAN INDIKASI PREEKLAMPSIA BERAT - Remilda Armika Vianti (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
Background: Patients post surgery sectio caesarea with indication of saverepereeclampsia is characterized by some specific condition such as an increase inblood pressure, urine protein and edema. Handling of medical therapy has becomeinseparable part in the management of these patients. Moreover, there is a nursingintervention can become an important part in maintain hemodinamic stability ofpatiens with non pharmacological therapies such as therapy of audio murottalQur'an.The purpose of the research: Determine the effect of the therapy of audiomurottal Qur’an in patients of post surgery of sectio caesarea with indication ofsavere preeclampsia in the hospital of Pekalongan.Research methods: The research design uses quasi experiment with pre and posttest with controul group. Research sample is patient of post surgery sectiocaesarea with indication severe preeclampsia in the hospital of Pekalongan, withtotal sample of 30 people. The sampling adapted to the characteristics the havebeen specified. Implementation of sampling with purposive sampling. DataAnalysis by Mann-whitney test.Results: There are 30 research samples consisted of 15 people the interventiongroup and the control group of 15 people. The results showed difference insystolic blood pressure drop significantly between the intervention group with acontrol group, marked with a P value (0.021) 0.05. There is a difference indiastolic blood pressure significantly between the intervention group and controlgroup, marked with a ρ value (0.00) 0.05.Suggestions: Nurses can provide interventions with non farmacological therapy istherapy of audio murottal Qur'an in patients post surgery sectio caesarea withindication of severe preeclampsia and conduct ongoing monitoring or evaluation.